The Role of Cognitive Reappraisal and Expressive Suppression toward Self-adjustment among Adolescence - Deby Elystiadi Dalimunthe; Fauziah Nasution (Universitas Ahmad Dahlan, 2023)
Self-adjustment is highly important in human life. It refers to the ability to adapt to social behavior and environment. Factors influencing an individual's ability to self-adjust include emotional regulation in the context of interaction, as self-adjustment is closely intertwined with it. The aim of this study is to examine the influence of cognitive reappraisal and expressive suppression on students' self-adjustment. The research sample consists of 104 tenth-grade high school students selected through a simple random sampling technique. Multiple linear regression analysis is employed in this study. The research findings reveal that the dimensions of cognitive reappraisal and expressive suppression have a significant influence on students' self-adjustment, accounting for 25.9%, while other factors account for the remaining 74.1%.Keywords: self-adjustment; emotional regulation; high school students